Gut microbiome in children with enthesitis‐related arthritis in a developing country and the effect of probiotic administration. (12th December 2016) - Aggarwal, A.; Sarangi, A. N.; Gaur, P.; Shukla, A.; Aggarwal, R.
Summary: In Asia, enthesitis‐related arthritis (ERA) is the most frequent category of juvenile idiopathic arthritis. ERA has a strong association with human leucocyte antigen (HLA)‐B27 and subclinical gut inflammation. In an HLA‐B27 transgenic rat model, the presence of Bacteroides bacteria in the gut appears to cause spondyloarthropathy (SpA). Thus, we studied gut microbiota in children with ERA. Stool specimens from 33 patients with ERA and 14 age‐matched healthy controls were studied; none had any gastrointestinal symptom, or had received a drug known to affect gut motility or microbiota in the preceding 6 weeks. From each specimen, a cDNA library for the V3 region of bacterial 16S rRNA was subjected to high‐throughput, massively parallel sequencing. Relationship of the specimens was studied using principal co‐ordinate analysis (PCoA), and abundances of various bacterial taxa and alpha diversity were compared between groups. In eight patients, a repeat faecal specimen was studied after 12 weeks of probiotic therapy. The 55 specimens yielded a median (range) of 397 315 (102 093–1 502 380) high‐quality reads each. In PCoA, gut microbiota from ERA showed a wider dispersion than those from controls. In patients, families Bacteroidaceae and Enterobacteriaceae were more abundant and Prevotellaceae were less abundant than in controls. Also, genera Bacteroides, Entercoccus and Klebsiella were over‐represented and genus Prevotella was under‐represented in ERA patients. Probiotic therapy led to a non‐significant increase in Prevotellaceae. Patients with ERA have a dysbiosis in the gut, with increased abundance of Bacteroides and reduction of Prevotella . Probiotic supplementation in a subset of patients did not reverse these changes significantly. Abstract : Gut microbiota from ERA showed a wider dispersion than those from controls In patients, genera Bacteroides, Entercoccus and Klebsiella were overrepresented, and genus Prevotella was under‐represented Probiotic therapy led to a non‐significant increase in Prevotellaceae.